Effect of fertilization with some major and minor elements on seedling and root rot in sesame plant and on some vegetative characteristics in glass house - Najwa Allethi (College of Education for Pure Sciences, 2006)
Sesame seeds were sown in pots contaminated with the root rot disease phathogens Pythium aphanidermatum, Fusarium solani, Macrophomina phaseolina,and supplemented with potassium, phosphorus or borax.These fertilizers considerably reduced the percentages and severity of infection of the seedlings with pre-and post-emergence damping off disease as compared to unfertilized pots. Moreover,The fertilizers also reduced the development of the root rot disease as scored four months after planting. This protective effect of fertilizers was most noticeable in plants treated with borax. Phpsphorous came second and potassium was third.